2015
DOI: 10.1039/c4cc08205b
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular assembly-induced yellow emission of 9,10-distyrylanthracene bridged bis(pillar[5]arene)s

Abstract: 9,10-Distyrylanthracene has been introduced to bridge two pillarenes to form a dimeric host, which can assemble into a linear supramolecular polymer upon cooperatively binding to a neutral guest linker, exhibiting yellow fluorescence emission in solution and solid states.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
42
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 119 publications
(42 citation statements)
references
References 79 publications
0
42
0
Order By: Relevance
“…The superior structures, facile functionalization, and typical host-guest properties of pillarenes stimulated a tremendous upsurge of interest in artifi cial transmembrane channels, [ 33,34 ] drug nanocarriers, [35][36][37][38][39][40] gas sorption, [ 41,42 ] MOFs, [ 43 ] sensing and detection, [ 44 ] stabilization of nanoparticles, biological applications, [ 45,46 ] etc. [47][48][49][50][51] Herein, benign activation mechanisms have been applied to targeted drug release systems constructed from monodisperse nanoMOFs (NMOFs) and carboxylatopillar [5]arene (CP5)-based stimuli-responsive supramolecular gates for CNS disease therapy for the fi rst time ( Figure 1 ). External heating as an important treatment of physical therapy in modern and traditional medicine has been introduced to regulate drug release from the gated nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…The superior structures, facile functionalization, and typical host-guest properties of pillarenes stimulated a tremendous upsurge of interest in artifi cial transmembrane channels, [ 33,34 ] drug nanocarriers, [35][36][37][38][39][40] gas sorption, [ 41,42 ] MOFs, [ 43 ] sensing and detection, [ 44 ] stabilization of nanoparticles, biological applications, [ 45,46 ] etc. [47][48][49][50][51] Herein, benign activation mechanisms have been applied to targeted drug release systems constructed from monodisperse nanoMOFs (NMOFs) and carboxylatopillar [5]arene (CP5)-based stimuli-responsive supramolecular gates for CNS disease therapy for the fi rst time ( Figure 1 ). External heating as an important treatment of physical therapy in modern and traditional medicine has been introduced to regulate drug release from the gated nanocarriers.…”
Section: Introductionmentioning
confidence: 99%
“…[13] In most cases, the partially functionalized pillar [5]arenes were obtained either by co-oligomacrocyclization of different 1,4-bis(alkoxy)-benzene monomers, [8a,9b,14] or through partial dealkylation followed by substitution. [7f,15] [5]arene.…”
Section: Introductionmentioning
confidence: 99%
“…Hitherto, a number of AIE‐active host–guest polymers based on pillararenes have been reported since 2014 for either fundamental study or specific applications. In 2014 and 2015, our research group reported two types of AIE‐active supramolecular polymers successively based on the host–guest recognition of pillararenes . After modifying two representative AIEgens (TPE and DSA) with pillar[5]arene (P5) to give TPE‐bridged P5 tetramer (TPE‐(P5) 4 ) and DSA‐bridged P5 dimer (DSA‐(P5) 2 ) ( Figure a,b), we further fabricated two host–guest systems with enhanced blue and yellow fluorescence, respectively, by constraining the intramolecular motions through supramolecular self‐assembly and polymerization between the AIEgen‐containing host molecules and neutral guest linkers.…”
Section: Aie‐active Supramolecular Nanocomplexes/polymersmentioning
confidence: 99%
“…iii) SEM image and iv) fluorescent image of the polymers. Adapted with permission . Copyright 2015, Royal Society of Chemistry.…”
Section: Aie‐active Supramolecular Nanocomplexes/polymersmentioning
confidence: 99%